Apprenticeships for greener economies and societies - (:unkn) unknown (Publications Office of the European Union, 2022)
“This publication draws from practices and research and provides insights into how apprenticeships can promote and react to a green economy and society, from small-scale modular curriculum adaptation, to more encompassing sectoral or regional approaches. As the green transition creates new skill needs across sectors and occupations, implications for preparing, reskilling and upskilling the workforce emerge for vocational education and training. Apprenticeships can help by providing opportunities to young people, as well as adults, to develop appropriate skills; at the same time, apprenticeships will also need to undergo changes in response to the green transition. Cedefop and the OECD decided to explore this two-way relationship through the 2021 joint symposium on Apprenticeships for greener economies and societies, and this publication. The practices and research presented show that apprenticeships demonstrate transformative potential for economies and societies, responding to the opportunities and challenges that may support a green recovery that leaves no one behind.” (editor; BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; G 2.5 Nachhaltigkeit; I 2.2 Europa; 370; Berufsausbildung; Nachhaltige Entwicklung; Green skills / grüne Kompetenzen; Kompetenzentwicklung; Lernort; Arbeitsmarkt; Chemische Industrie; Europa